Rasgando uniformes e descosturando normas de gênero no espaço escolar - Menezes, Carlos André Araújo (2019)
Writing about gender and sexuality in basic education is a challenge that requires theoretical and political choice that dares "to be suspicious of definitive certainties" (LOURO 2007, p. 237), so this Master's thesis in Education is an act of courage and daring, since Intentionally assumes a self-etnografic tone, where the narratives of a researcher teacher and the narratives of students and colleagues Professors are mixed, in an attempt to perceive how the body expression of gay and lesbian students in the school space Contributed to the expansion of debates on gender and sexual diversity in school. In the case of the State College Dr. Antônio Garcia Filho, located in the city of Umbaúba-SE; Body expression was understood as the creation of verbal and non-verbal communication, through community manifestations suggested from gestures, facial expressions and other postures in the halls and classrooms of the same school, which composed some school scenes analyzed in this work. In this trajectory the following contributions were essential: Le Breton (200), Bento (2014) Buttler (2010), Ribera (2017), besides other authors as: Foucault (2017), Louro (2014), Silva 2013), which helped to deepen the debate about power-knowledge relations and the new ways of looking at education and the subjects that are part of it. The specific objectives were so thought: Reflect the paths and obstacles encountered in the course of schooling students; and to verify the signs of destabilization to the norms of gender from the presence of students in the school in the State School Dr. Antônio Garcia Filho; and finally to identify how their existence in basic education has led to curricular changes and ways of doing and living the gender in school. Throughout the text I adopted the metaphor of sewing, a metaphor attached to my plastic senses of understanding the world and my profession as a teacher - the taboos, the weaknesses and potentialities of the discussion provoked in me controversial and confused feelings, given the fluidity of what was being studied, a difficult game of many (in) certainties. The production of the data investigated was developed from the approach of the poststructuralist methodology in education, with narrative interviews recorded in audios and videos, triggered by the "look, listen and feel" exercise. and the "other ways" of doing science (Souza, 2018). In the end, the results pointed to the need for the current school, that one and others, to promote less exclusive and more inclusive educational processes that embrace difference. As also the interviews pointed to the need for the current school, that one and others, to promote less exclusive and more inclusive educational processes, based on the appreciation of difference. The narratives pointed out the emergence of a movement and pedagogical practices that are based on the school curriculum of the aforementioned college, based on the non-strangeness of the non-intelligible bodies. A curriculum with pedagogical potency inclusive of / in difference and with spaces of binary genre unlearning.